Coordinate system and combinatorial objects (an example of a generalized quadrangle) - Medvedev, V. K. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
By using a generalized quadrangle as an example, we verify the assumption that coordinate systems (different from the standard Cartesian coordinate system) exist not only in an arbitrary projective plane, where they are determined by a nondegenerate quadrangle, but also in some other combinatorial objects.